Utilizing Biomimetic Polymers for Innovations in Drug and Gene Delivery - Vediya, Pratik; Mehta, Dharmik; Pandya, Jemini; Gadavala, Sarah; Bhatiprollu, Medha; Aerukala, Vasanthi (Indian Journal of Pharmaceutical Education and Research, 2026)
Biomimetic polymers are increasingly being explored in advanced drug and gene delivery research due to their ability to imitate the structure and function of natural biological systems. Increased biocompatibility, targeted delivery, and controlled release (with time-dependent release kinetics) make them ideally suited for therapeutic applications. These polymers imitate the features of cell membranes, proteins and other biological entities, and have shown greater biocompatibility, targeted delivery, and controlled release kinetics widely tunable to allow for a variety of therapeutic applications; including cancer therapy, regenerative medicine, and gene therapy, biomimetic polymers can facilitate the targeted and efficient transport of therapeutic agents, including small molecules (e.g., drugs), nucleic acids and proteins, in a manner that has helped overcome barriers associated with existing delivery systems. The materials design and synthesis of biomimetic polymers have become much better recent years, allowing their full potential as therapeutics to be realized, even though issues related to stability, targeting, and ways to efficiently manufacture it to scale for clinical application remain. Biomimetic polymers possess considerable potential to change drug and gene delivery paradigms, with opportunities to enhance clinical outcomes and personalize medicine. Given these challenges, we can only begin to imagine what we can achieve with biomimetic polymers in the future, and continue effort into addressing existing limitations while continuing to realize their promise will be necessary to allow their transformation of chemotherapy delivery vehicles and other therapeutic delivery systems. This review highlights recent advancements biomimetic polymer technologies, and highlights their considerable ability to impact the improvement of efficacy, targeting and safety of drug and gene delivery technologies. It also explores current obstacles and prospective advancements in the field, emphasizing the significant potential of these materials to revolutionize drug delivery systems and improve clinical outcomes.
Keywords: Biological Molecule and amp; Biomimetic Polymer; Gene Delivery; Structure